2018
DOI: 10.1634/theoncologist.2017-0465
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Study of Metformin plus Paclitaxel/Carboplatin/Bevacizumab in Patients with Chemotherapy-Naïve Advanced or Metastatic Nonsquamous Non-Small Cell Lung Cancer

Abstract: The anticancer effects of metformin continue to be elucidated. To the authors' knowledge, this is the first trial in nondiabetic advanced non-small cell lung cancer patients to show a significant change in outcome with the addition of metformin to standard first-line chemotherapy. Well tolerated and widely available, metformin is a drug that should be considered for further study in the lung cancer treatment landscape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 25 publications
0
74
1
Order By: Relevance
“…2,3 Outcomes for patients with metastatic NSCLC are poor, with only 4% of patients surviving 5 years after diagnosis. 6,7 Atezolizumab is an IgG1 monoclonal antibody that binds to PD-L1 and blocks its interactions with PD-1 and B7-1 (also known as CD80) receptors. 6,7 Atezolizumab is an IgG1 monoclonal antibody that binds to PD-L1 and blocks its interactions with PD-1 and B7-1 (also known as CD80) receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Outcomes for patients with metastatic NSCLC are poor, with only 4% of patients surviving 5 years after diagnosis. 6,7 Atezolizumab is an IgG1 monoclonal antibody that binds to PD-L1 and blocks its interactions with PD-1 and B7-1 (also known as CD80) receptors. 6,7 Atezolizumab is an IgG1 monoclonal antibody that binds to PD-L1 and blocks its interactions with PD-1 and B7-1 (also known as CD80) receptors.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Before the introduction of targeted therapies and immunotherapy, platinum-doublet chemotherapy with or without bevacizumab was the standard of care for previously untreated patients with metastatic, nonsquamous NSCLC. 6,7 Atezolizumab is an IgG1 monoclonal antibody that binds to PD-L1 and blocks its interactions with PD-1 and B7-1 (also known as CD80) receptors. 4 The IMpower150 trial evaluated the combination of atezolizumab, bevacizumab, carboplatin, and paclitaxel (ABCP) for previously untreated patients with metastatic, nonsquamous NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The 1‐year PFS on arm A (carboplatin, paclitaxel, and bevacizumab with metformin) was 47% (95% CI, 25%‐88%), which exceeded the historical control 1‐year PFS of 15%. Median overall survival of patients treated on arm A was 15.9 months (95% CI, 8.4‐not available) and 13.9 months (95% CI, 12.7‐not available) on arm B (carboplatin, paclitaxel, and bevacizumab without metformin) . Disappointingly, the results indicated that there were no significant differences in toxicity between the two study arms.…”
Section: Combination Of Metformin With Antibodiesmentioning
confidence: 98%
“…It was approved in 2004 in combination with chemotherapy for metastatic colorectal cancer and now it is used in the treatment of numerous cancer types-metastatic breast cancer, renal cell carcinoma, advanced epithelial ovarian cancer, non-squamous NSCLC [75]. Combination of metformin with bevacizumab was found to be effective in the treatment of ovarian cancer and metastatic non-squamous NSCLC in combination with chemotherapy [76,77].…”
Section: Metformin: Combination With Targeted Therapiesmentioning
confidence: 99%